Risk Analysis of Time Delay in The Sumbawa Shrimp Pond Farming Project - Muhamad Rizal; Novika Candra Fertilia (Journal of World Conference (JWC), 2021)
Sekar Laut Group is opening a new land of around 1,000 hectares for shrimp ponds in the Sumbawa area, West Nusa Tenggara. The land in Sumbawa is suitable for shrimp farming because the water is considered cleaner and has no pollution. during the construction process, there were various kinds of obstacles that resulted in work delays of around 23% of the agreed schedule. Therefore, research is conducted to determine the dominant risk that affects the project's time performance and provide risk mitigation so that the risks that occur can be minimized. This research uses quantitative research methods by distributing questionnaires to related parties and testing the validity and reliability using SPSS version 25 software. The data processing method uses risk value data analysis to determine which risks are classified as high risk. The number of risks identified in this research were 35 risks consisting of 33 risks based on literature studies and 2 new findings risks. based on 35 risks distributed to respondents, there are 2 risks that are categorized as high risk. 1 (one) risk comes from a literature study is the subcontractor's poor performance, and 1 (one) other risk comes from the risk of new findings from expert advice is the large amount of repair work due to the earthquake.